A Positive Feedback Loop between ATOH7 and a Notch Effector Regulates Cell-Cycle Progression and Neurogenesis in the Retina - Florence Chiodini (Cell Reports, 2013)
The HES proteins are known Notch effectors and have long been recognized as important in inhibiting neuronal differentiation. However, the roles that they play in the specification of neuronal fate remain largely unknown. Here, we show that in the differentiating retinal epithelium, the proneural protein ATOH7 (ATH5) is required for the activation of the transcription of the Hes5.3 gene before the penultimate mitosis of progenitor cells. We further show that the HES5.3 protein slows down the cell-cycle progression of Atoh7-expressing cells, thereby establishing conditions for Atoh7 to reach a high level of expression in S phase and induce neuronal differentiation prior to the ultimate mitosis. Our study uncovers how a proneural protein recruits a protein known to be a component of the Notch signaling pathway in order to regulate the transition between an initial phase of selection among uncommitted progenitors and a later phase committing the selected progenitors to neuronal differentiation.